Agresión sexual en el Ecuador - Fuertes, Alexandra A. (2020)
Sexual assault is an act of significant cruelty against the victim and their freedom sexual; breaks into their privacy, compromising their physical, psychological and Social. Different factors are involved in the manifestation of this crime, generating consequences that vary according to the characteristics of those involved and especially, depending on the context in which this situation occurs, which for the present study comes to be the Ecuadorian territory, with its various socio- cultural. The approach to sexual assault is very complex because it has to be analyzed objective and subjective elements of the victim, who may be very sensitive and experience great affectation when confronted with what happened and take on a legal case.